2020
DOI: 10.1002/er.5673
|View full text |Cite
|
Sign up to set email alerts
|

Improved dark fermentation of cane molasses in mesophilic and thermophilic anaerobic fluidized bed reactors by selecting operational conditions

Abstract: Improved dark fermentation of cane molasses in mesophilic and thermophilic anaerobic fluidized bed reactors by selecting operational conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…thermosaccharolyticum strain CT72. Generally, high-temperature conditions are suitable for the growth of thermophilic butyrate-producing bacteria and butyric-acid-type fermentation. Although the thermophilic temperature was also investigated in this study, the fermentation type was mostly the acetic acid type in stage V, which can be attributed to the dominant microorganism, T. thermosaccharolyticum strain CT72, which produces hydrogen in thermophilic acetic-acid-type fermentation.…”
Section: Resultsmentioning
confidence: 94%
“…thermosaccharolyticum strain CT72. Generally, high-temperature conditions are suitable for the growth of thermophilic butyrate-producing bacteria and butyric-acid-type fermentation. Although the thermophilic temperature was also investigated in this study, the fermentation type was mostly the acetic acid type in stage V, which can be attributed to the dominant microorganism, T. thermosaccharolyticum strain CT72, which produces hydrogen in thermophilic acetic-acid-type fermentation.…”
Section: Resultsmentioning
confidence: 94%
“…Different operational factors affect the fermentation process, yield, composition and concentration of VFAs produced from industrial and municipal waste (Lee et al 2014). Some of these operational factors include pH, temperature, retention time, additives, inoculum type, and substrate type (Ferreira et al 2020). Researchers investigated the factors mentioned above individually, and very few researchers investigated the interactive effects of some of these operational parameters (Lee et al 2014).…”
Section: Operating Conditions Affecting Dark Fermentation and Vfa Pro...mentioning
confidence: 99%
“…Moreover, various organic acids and other compounds with different applications (foods, pharmaceuticals, and chemicals) can be generated during the biological production of hydrogen. Most studies have reported that biohydrogen production generates intermediates such as acetic acid, propionic acid, butyric acid, succinic acid, formic acid, butanediol, and acetone [15][16][17][18][19][20]. These compounds are of special interest because of their high market value [21,22], especially butyric and lactic acid, which are used as precursors of industrial thermoplastics [23] and biodegradable polymers [24,25].…”
Section: Introductionmentioning
confidence: 99%